1994
DOI: 10.1093/tropej/40.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Comparing Hospital to Ambulatory Rehabilitation of Malnourished Children in Niger

Abstract: This study compared hospital to ambulatory nutritional rehabilitation outcomes and costs. Following a hospital stay to resolve initial acute medical conditions, 100 malnourished children (54 per cent male, ages 5 to 28 months) in Niger were randomly assigned to either hospital or ambulatory nutritional rehabilitation. Anthropometric measures were assessed at 15, 30, 60, 90 and 180 days post-randomization. Following randomization, the hospital group received a mean of 12.9 days of hospital rehabilitation and 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 0 publications
0
66
0
Order By: Relevance
“…A literature search in Medline and Google scholar without period restriction was conducted using the term "protein energy malnutrition", "protein caloric malnutrition", "severe malnutrition", "marasmus", "kwashiorkor", "mortality" and "after recovery", "postdischarge" or "long term" Eight studies examining post-discharge mortality were retrieved (Chapko et al, 1994;Pecoul et al, 1992;Reneman and Derwig, 1997;Roosmalen-Wiebenga et al, 1987;Khanum et al, 1998;Kerac, 2010, Hennart et al, 1987Keet et al, 1971) but five studies were excluded either because the definition of SAM was different from what is currently used (n = 2) or because of incomplete data for the calculation of the incidence of deaths (n = 3) (Chapko et al, 1994;Roosmalen-Wiebenga et al, 1987;Kerac, 2010;Hennart et al, 1987;Keet et al, 1971). Among those included in this paper, the first study was carried out in Tahoua, a region of Niger.…”
Section: Description Of Cohorts From Papers Identified Through a Litementioning
confidence: 99%
See 1 more Smart Citation
“…A literature search in Medline and Google scholar without period restriction was conducted using the term "protein energy malnutrition", "protein caloric malnutrition", "severe malnutrition", "marasmus", "kwashiorkor", "mortality" and "after recovery", "postdischarge" or "long term" Eight studies examining post-discharge mortality were retrieved (Chapko et al, 1994;Pecoul et al, 1992;Reneman and Derwig, 1997;Roosmalen-Wiebenga et al, 1987;Khanum et al, 1998;Kerac, 2010, Hennart et al, 1987Keet et al, 1971) but five studies were excluded either because the definition of SAM was different from what is currently used (n = 2) or because of incomplete data for the calculation of the incidence of deaths (n = 3) (Chapko et al, 1994;Roosmalen-Wiebenga et al, 1987;Kerac, 2010;Hennart et al, 1987;Keet et al, 1971). Among those included in this paper, the first study was carried out in Tahoua, a region of Niger.…”
Section: Description Of Cohorts From Papers Identified Through a Litementioning
confidence: 99%
“…A commonly cited reason behind this resistance is the supposed persistence of a high risk of mortality after recovery from SAM once the patient has exited the treatment programme (Ashworth, 2006). Data on the longer term mortality associated with discharge from inpatient therapeutic feeding centres is variable; some studies have reported a cumulative mortality rate of 1 to 1.5 years after discharge of up to 41% (Ashworth, 2006;Chapko et al, 1994;Pecoul et al, 1992;Reneman and Derwig, 1997;Roosmalen-Wiebenga et al, 1987), whilst others have reported lower figures of 2.3% after 12 months of follow up, and 4.1% after 1.5 years of follow up (Bahwere et al, 2008;Khanum et al, 1998). An earlier study reported a mortality of 1.5%, 12 months after discharge among children treated using the domiciliary approach (Khanum et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…62 were partially funded by a US governmental education fellowship, Khanum and colleagues 65 were supported by a UK charity and the UK government and Ciliberto and colleagues 63 received funding from the United Nations, a US charity and hospital foundation, a UK humanitarian organisation and the US government. Chapko and colleagues 62 compared inpatient with daily ambulatory rehabilitation, and two of the trials 63,64 investigated hospital-and home-based rehabilitation (differing, however, in the level of support provided).…”
mentioning
confidence: 99%
“…Chapko and colleagues 62 compared inpatient with daily ambulatory rehabilitation, and two of the trials 63,64 investigated hospital-and home-based rehabilitation (differing, however, in the level of support provided). These three trials [62][63][64] evaluated alternative settings for the rehabilitation phase of treatment for malnourished children, after an initial phase of hospital care common to both treatment arms. In contrast, the fourth trial, by Khanum and colleagues, 65 had three trial arms to compare inpatient care with daily ambulatory care for both the initial and the rehabilitation phases of treatment for children with SAM, and with home rehabilitation (after daily ambulatory care during the initial phase of treatment).…”
mentioning
confidence: 99%
See 1 more Smart Citation